Investigating Students’ Perspective on the Use of SpeechAce Platform in Pronunciation Skills of English Department Freshman Students - Dilla Fransisca Rosita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study aimed to identify the obstacles students experienced when using SpeechAce, an artificial intelligence-based website designed to assist in learning English pronunciation. In addition, this study also aimed to investigate the role of SpeechAce in supporting lecturers in English learning at English department. The method used in this study was a mixed method with a convergent parallel design conducted in three stages. On the first day, freshman students were introduced to SpeechAce and asked to practice independently at home. On the second day, students engaged in a collaborative practice using the vowels 1 feature in SpeechAce. The last day was the evaluation and filling of questionnaires to collect data related to student experience and responses. The results of students’ responses showed that some students experience network constraints when using campus WiFi to access SpeechAce. However, such problems can be solved by using private data networks that provide faster access. This is because SpeechAce requires stable network connectivity. Acquisition of data collected by field notes, questionnaires, and documentation techniques produce that SpeechAce and lecturers complement each other to create a more effective learning experience. SpeechAce helps lecturers in teaching speaking skills with a live evaluation feature.